Mindenütt idegen - Katona, Zsuzsa; Nyeste, Péter (Hungary : Aster Film, 2007)
Refugee children in Hungary whose only opportunity for a holiday is the yearly camp organized by Menedék, and NGO protecting the rights of refugees in Hungary.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films